2018
DOI: 10.1007/s10903-018-0746-1
|View full text |Cite
|
Sign up to set email alerts
|

Guards in Prisons: A Risk Group for Latent Tuberculosis Infection

Abstract: To determine the prevalence and incidence of LTBI among prison guards and to the risk factors associated with infection. Two male prisons in Medellín and Itaguí, Colombia. A cohort study was conducted in adult prison guards that consented to participate. Exclusion criteria included: previous or current active TB, or conditions that preclude TST administration. We screened 194 guards and completed 155 TST administrations. The prevalence of LTBI was 55.8% in prison one, and 39.1% in prison two. The risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Additionally, several studies from the analysis by Baussano and colleagues 6 included guards and prison staff, 35 who have a lower risk of infection and disease than prisoners. 36 The elevated M tuberculosis infection rates seen in incarcerated populations are concerning and could impede interventions that do not directly prevent transmission in areas with a heavy tuberculosis burden. 5 , 37 These results suggest that prisoners are at high risk of developing tuberculosis in every global region and should be prioritised for tuberculosis screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several studies from the analysis by Baussano and colleagues 6 included guards and prison staff, 35 who have a lower risk of infection and disease than prisoners. 36 The elevated M tuberculosis infection rates seen in incarcerated populations are concerning and could impede interventions that do not directly prevent transmission in areas with a heavy tuberculosis burden. 5 , 37 These results suggest that prisoners are at high risk of developing tuberculosis in every global region and should be prioritised for tuberculosis screening.…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review and metaanalysis followed the Preferred Reporting Items for Systematic Reviews and MetaAnalyses (PRISMA) guidelines (appendix pp [35][36][37]. 15 This study is registered with PROSPERO, CRD42018104463.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…In addition, we did not evaluate prison staff, family members or visitors which could increase the number of TB cases detected and consequently increase the prevalence of active TB. Recently, one study reported that security guards may serve as a bridge population for TB transmission between prison and community [68].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, researches addressing occupational health on prison staff members have contributed to describe different adverse physical and mental health outcomes, but scarcely relating them to burnout [56]. As for Colombian correctional officers, only two previous researches on this regard were found through a literature review, both describing a high risk of suffering infectious diseases, such as tuberculosis, and determining that the risk of this kind of illnesses could be up to 20 times greater for prison staff when compared to the general population [60,61]. No further research on other professional health issues of correctional officers was found during the literature review.…”
Section: Introductionmentioning
confidence: 99%